Molecular cloning of the gene for the allatostatin family of neuropeptides from the cockroach Diploptera punctata. - Donly, B C (1993)
Allatostatins (ASTs) are insect neuropeptides that inhibit juvenile hormone biosynthesis by the corpora allata. We have isolated a cDNA from the cockroach Diploptera punctata that encodes a 41.5-kDa precursor polypeptide containing the AST family of peptides. Translation of the cDNA revealed a 370-amino acid pre-pro-peptide consisting of 13 AST-type peptides and appropriate processing sites for endoproteolytic cleavage and amidation. The 13 potential AST sequences are characterized by the C-terminal AST corestructure Phe-Gly-Leu-NH2, with only one exception. Separating the clustered ASTs in the precursor, three acidic spacer regions are found. Contained within the largest of these are two potentially related peptides that may also be processed. Southern blot analysis revealed the presence of a single copy of the AST gene per haploid genome, as well as the probability that the gene may be present in at least two allelic forms. In situ hybridization indicated the AST-encoding gene is expressed in neurosecretory cells of D. punctata brain.